Diffuse functional brain disconnection syndrome in critically ill patients with COVID-19. Issue 7 (July 2021) - Iacovazzo, Carmine; Vargas, Maria; Tedeschi, Enrico; De Simone, Anna; Brunetti, Arturo; Servillo, Giuseppe
Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is most closely related to severe respiratory syndrome; however, recent reports showed that it is capable of causing neurological disease. Here we report a case-series of 4 critically ill COVID-19 patients who recovered from pneumonia but showed serious neurological symptoms and eventually died.